2021
DOI: 10.3390/ph14090927
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Pazopanib in Patients and Determination of Target AUC

Abstract: Pazopanib is a potent multi-targeted kinase inhibitor approved for the treatment of advanced renal cell carcinoma and soft tissue sarcoma. The pharmacokinetics of pazopanib is characterized by a significant inter- and intra-patient variability and a target through plasma concentration of 20.5 mg·L−1. However, routine monitoring of trough plasma concentrations at fixed hours is difficult in daily practice. Herein, we aimed to characterize the pharmacokinetic (PK) profile of pazopanib and to identify a target ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The demographic and biological characteristics of that population were similar to our cohort (median age 53 years old, normal liver, and renal function). Although the population from Yu et al included more male patients (78%) than our cohort (52%), sex is not a significant covariate on pazopanib PK, as previously reported by Ozbey et al [10]., which confirmed that the model by Yu et al could be used to predict PK parameters in our STS patient cohort.…”
Section: Pharmacokinetic Assessmentssupporting
confidence: 88%
See 2 more Smart Citations
“…The demographic and biological characteristics of that population were similar to our cohort (median age 53 years old, normal liver, and renal function). Although the population from Yu et al included more male patients (78%) than our cohort (52%), sex is not a significant covariate on pazopanib PK, as previously reported by Ozbey et al [10]., which confirmed that the model by Yu et al could be used to predict PK parameters in our STS patient cohort.…”
Section: Pharmacokinetic Assessmentssupporting
confidence: 88%
“…Blood samples were drawn at steady state every two weeks for the first three months and then monthly. Given that the half-life of pazopanib is approximatively 31 h, the steady state was considered to be reached after at least 15 days following either treatment initiation or dosage adjustment [10,20]. Blood was collected in 5-mL lithium heparinized Vacutainer tubes at any time over the administration interval.…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pazopanib is metabolized to a lesser extent by CYP1A2 and CYP2C8. Similarly, pazopanib is a substrate for P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) 1,9 ; therefore, genetic polymorphisms of these transporters may influence treatment outcomes or the toxicity of some drugs, including TKIs. 10,11 Elimination primarily occurs through feces, with an elimination half-life of approximately 31 hours.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Elimination primarily occurs through feces, with an elimination half-life of approximately 31 hours. 1,9 Although the differential pharmacokinetics of pazopanib between patients may be at least in part attributed to any of these factors, sex does not seem to affect pazopanib exposure. 3,12…”
Section: Introductionmentioning
confidence: 99%